PENERAPAN PENDEKATAN SAINTIFIK MATERI BANGUN RUANG UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI SDN LIDAH WETAN II/462 - Puji Lestari, Risa (Universitas Nahdlatul Ulama Pasuruan, 2020)
An effective learning process requires the teacher to determine teaching strategies so that students can learn actively. One step that must be done is the application of innovative learning models. The learning model developed in this research is believed to have high relevance is a scientific learning approach model. Observations made by the author, still found learning that has not been able to trigger student activity and there are still many students who score below the KKM. This study aims to describe the application of learning with a scientific approach to improve student learning outcomes in the VID class. The results showed that student learning outcomes improved. In the stage before improvement there were only 6 of 29 students or 21% who experienced mastery learning, increased to 18 of 29 students or 62.06% who experienced mastery in the first cycle, and experienced a significant increase to 25 of 29 students or 86.20 % of students who have mastery completing cycle II, and classically have completed mastery learning which is more or equal to 85% of students who have completed. So through the application of ascientific approach to the subject matter of building mathematics subjects in the VID grade at SD Negeri Lidah Wetan II / 462 Surabaya in the academic year 2019/2020 it can improve student learning outcomes.